How to Arrive at Peace in Deeply Divided Societies? Using Deliberation to Refine Consociational TheoryHow to Arrive at Peace in Deeply Divided Societies? Using Deliberation to Refine Consociational Theory - Jürg Steiner; Maria-Clara Jaramillo (Journal of Deliberative Democracy, 2019)
In the 1960s, consociational theory was developed to explain how deeply divided societies can arrive at peace. The theory had, on the one hand, an institutional component with an emphasis on power-sharing institutions and, on the other, a cultural component stressing the importance of a spirit of accommodation. Initially, the theory was based on case studies of countries like Austria, Belgium, the Netherlands and Switzerland, which allowed dealing with both institutional and cultural aspects. Later on, when the theory was tested with a large sample of countries, the cultural aspect was increasingly neglected, because it was difficult to empirically operationalize. The key argument of the article is that the concept of deliberation helps emphasize the cultural aspect of consociational theory, in the hopes of refining, not replacing, consociational theory.